Do anxiety, depression, and intolerance of uncertainty contribute to social problem solving in adult women with anorexia nervosa?. Issue 6 (9th April 2020) - Sternheim, Lot; Danner, Unna; van Elburg, Annemarie; Harrison, Amy
Abstract: Introduction: Inefficient problem solving in the social domain may be one of the difficulties underlying the interpersonal challenges thought to maintain anorexia nervosa (AN). However, past studies have neglected to control for depression, anxiety, and intolerance of uncertainty (IU), which are known to contribute to social problem solving. Methods: This study aimed to investigate whether adults with AN would show differences in social problem solving on an experimental task (Means‐End Problem Solving; MEPS) and report differences in their attitudes (positive, negative) toward social problem solving and their use of social problem‐solving styles (rational, impulsive–careless, avoidant) on the Social Problem‐Solving Inventory Revised (SPSRI) compared to a non‐AN control group. Results: Seventy‐four adult women took part (30 with AN and 44 non‐AN controls), and data show that those with AN generated significantly less effective solutions on the MEPS ( d  = 1.96) reported overall poorer social problem solving on the SPSRI ( d  = 0.58), reporting more negative and less positive attitudes toward social problem solving, and less impulsive and more avoidant social problem‐solving styles. However, those with AN did not differ from controls in being able to rationalize social problems. Once depression (Beck Depression Inventory: BDI), state anxiety (State‐Trait Anxiety Inventory: STAI), and IU (Intolerance of Uncertainty Scale‐12; IUS‐12) were included as covariates, these differences were no longer significant, suggesting that comorbid depression, anxiety, and IU symptoms may contribute to social problem solving in AN. Conclusions: There was no specific effect of depression. Treating anxiety and IU might help to improve social problem solving and enable people with AN to be able to better access social support to aid their recovery. Abstract : Compared to a non‐AN control group, women with AN showed poorer social problem solving abilities, as well as more dysfunctional social problem styles and attitudes. Anxiety and intolerance of uncertainty contributed to these social problem‐solving processes and outcomes.